Extensores à base de gema de ovo e lipossomas na criopreservação de semen colhido por massagem retal associado ou não ao uso de eletroejaculador em bufalos - Almeida Filho, Rogério Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Este estudo avaliou o uso de diferentes diluentes e métodos de colheita de sêmen sobre a qualidade espermática pós-descongelamento em búfalos da raça Murrah. Foram obtidos 22 ejaculados de dez animais em 98 tentativas, sendo selecionados para criopreservação apenas os com motilidade total ≥75%, vigor ≥3 e concentração ≥30x10⁶ espermatozoides/mL. Os ejaculados foram divididos entre dois diluentes: gema de ovo (BotuBov®) e lipossoma (OptiXcell®). Após congelamento e descongelamento (37 °C por 30 segundos), avaliou-se a cinética espermática e a integridade celular por citometria de fluxo. O grupo diluído com lipossoma apresentou maior velocidade curvilínea (VCL: 138,5 ± 62,8 mm/s vs. 109 ± 24,9 mm/s; P=0,02) e maior proporção de espermatozoides com movimento lento (SLOW: 7,7 ± 6,7% vs. 5,6 ± 6,1%; P=0,03). Por outro lado, o grupo com gema de ovo apresentou valores superiores para frequência de batimento de cauda (BCF: 30,9 ± 5,5 Hz vs. 24,8 ± 9,6 Hz; P=0,002), retilinearidade (STR: 87,1 ± 7% vs. 73,8 ± 18,5%; P=0,0002) e linearidade (LIN: 57,8 ± 10,3% vs. 46,1 ± 13,3%; P=0,0006). Após 3 horas de incubação a 37 °C, a linearidade permaneceu maior no grupo com gema de ovo (LIN: 40,7 ± 29,6% vs. 27,5 ± 23,9%; P=0,03). Dos 22 ejaculados, 17 foram obtidos por massagem retal (TRM) e 5 por TRM com eletroejaculador (TRM+EL). O método TRM+EL com diluente lipossomal resultou em maior VCL (169,5 ± 53,6 mm/s) e amplitude de deslocamento lateral da cabeça (ALH: 6,7 ± 1,4 mm) comparado ao TRM com diluente de gema de ovo (VCL: 117,6 ± 25,7 mm/s; P=0,01; ALH: 4,9 ± 0,8 mm; P=0,01). Já o TRM+EL com gema de ovo apresentou maior STR (93 ± 3% vs. 47,1 ± 37,6%; P=0,0001) e LIN (66 ± 6,6% vs. 43 ± 5,6%; P<0,0001). A citometria revelou maior preservação da integridade espermática com gema de ovo (MPAI: 29,75 ± 13,1%; MPAL: 8,8 ± 7,3% vs. 22,62 ± 16,7%). Conclui-se que o diluente à base de gema de ovo foi mais eficaz na manutenção da cinética e integridade espermática, e que a massagem retal é um método viável para colheita em búfalos.

This study evaluated the use of different diluents and semen collection methods on post-thawing sperm quality in Murrah buffaloes. Twenty-two ejaculates were obtained from ten animals in 98 attempts, and only those with total motility ≥75%, vigor ≥3 and concentration ≥30x10⁶ sperm/mL were selected for cryopreservation. The ejaculates were divided between two diluents: egg yolk (BotuBov®) and liposome (OptiXcell®). After freezing and thawing (37°C for 30 seconds), sperm kinetics and cell integrity were evaluated by flow cytometry. The liposome-diluted group showed higher curvilinear velocity (VCL: 138.5 ± 62.8 mm/s vs. 109 ± 24.9 mm/s; P=0.02) and higher proportion of slow-moving sperm (SLOW: 7.7 ± 6.7% vs. 5.6 ± 6.1%; P=0.03). On the other hand, the egg yolk group showed higher values for tail beat frequency (BCF: 30.9 ± 5.5 Hz vs. 24.8 ± 9.6 Hz; P=0.002), rectilinearity (STR: 87.1 ± 7% vs. 73.8 ± 18.5%; P=0.0002) and linearity (LIN: 57.8 ± 10.3% vs. 46.1 ± 13.3%; P=0.0006). After 3 hours of incubation at 37°C, linearity remained higher in the egg yolk group (LIN: 40.7 ± 29.6% vs. 27.5 ± 23.9%; P=0.03). Of the 22 ejaculates, 17 were obtained by rectal massage (RMT) and 5 by RMT with electroejaculator (RMT+EL). The RMT+EL method with liposomal diluent resulted in greater VCL (169.5 ± 53.6 mm/s) and amplitude of lateral displacement of the head (ALH: 6.7 ± 1.4 mm) compared to RMT with egg yolk diluent (VCL: 117.6 ± 25.7 mm/s; P=0.01; ALH: 4.9 ± 0.8 mm; P=0.01). On the other hand, RMT+EL with egg yolk presented greater STR (93 ± 3% vs. 47.1 ± 37.6%; P=0.0001) and LIN (66 ± 6.6% vs. 43 ± 5.6%; P<0.0001). Cytometry revealed greater preservation of sperm integrity with egg yolk (MPAI: 29.75 ± 13.1%; MPAL: 8.8 ± 7.3% vs. 22.62 ± 16.7%). It is concluded that the egg yolk-based extender was more effective in maintaining sperm kinetics and integrity, and that rectal massage is a viable method for collection in buffaloes. Keywords: Bubalus bubalis, semen collection, rectal massage, eletroejaculator
Egg yolk and liposome-based extenders in the cryopreservation of semen collected by rectal massage associated or not with the use of electroejaculator in buffaloes
Keywords: Bubalus bubalis; Colheita seminal; Massagem retal; Eletroejaculador